The deformation of an elastic rod with a clamp sliding along a smooth and curved profile. (September 2015) - Misseroni, D.; Noselli, G.; Zaccaria, D.; Bigoni, D.
Abstract: The design of compliant mechanisms is crucial in several technologies and relies on the availability of solutions for nonlinear structural problems. One of these solutions is given and experimentally validated in the present article for a compliant mechanism moving along a smooth curved profile. In particular, a deformable elastic rod is held by two clamps, one at each end. The first clamp is constrained to slide without friction along a curved profile, while the second clamp moves in a straight line transmitting its motion through the elastic rod to the first clamp. For this system it is shown that the clamp sliding on the profile imposes nontrivial boundary conditions (derived via a variational and an asymptotic approach), which strongly influence buckling and nonlinear structural behavior. Investigation of this behavior shows that a compliant mechanism can be designed, which gives an almost neutral response in compression. This behavior could easily be exploited to make a force limiting device. Finally a proof-of-concept device was constructed and tested showing that the analyzed mechanical system can be realized in practice and it behaves tightly to the model, so that it can now be used in the design of machines that use compliant mechanisms.